The incidence and mortality rate of catheter-related neonatal pericardial effusion: A meta-analysis - Wang, Jingyi; Wang, Qing; Liu, Yanxia; Lin, Zebin; Janjua, Muhammad Usman; Peng, Jianxiong; Du, Jichang (Medicine (Baltimore), 2022)
Neonatal pericardial effusion (PCE) is one of the most severe complications of central catheters in neonates with its rapid progression and high mortality. We aim to estimate the overall incidence and mortality of catheter-related neonatal PCE, more importantly, to identify possible predictors for clinical reference. We searched MEDLINE, Embase, Cochrane Library, Web of Science, china national knowledge infrastructure, Wanfang Data, and Sinomed databases for subject words "central catheter," "neonate," "pericardial effusion" and their random words till June 8, 2020. This meta-analysis is based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Possible predictors of occurrences and deaths were extracted and assessed cooperatively. The pooled incidence rate of catheter-related neonatal PCE was calculated using a random effects model. Twenty-one cohort studies and 99 cases were eligible. Pooled incidence is 3·8‰[2.2‰, 6.7‰]. Polyurethane catheters generate significantly more neonatal PCE than silicone counterparts (P < .01). 27% of the patients die. The mortality of patients with bradycardia is higher than others (P < .05). Catheters with a guidewire result in more deaths than umbilical venous catheter (UVC) and peripherally inserted central catheters (PICC) (P < .05). Without pericardiocentesis, mortality increases (P < .01). The difference of deaths between reposition and removing the catheter is insignificant (P > .05). Central catheters in Seldinger Technique (with a guidewire) put neonates at greater risk of PCE and consequent death. Silicone catheters excel at avoiding deadly catheter-related PCE, which could be a better choice in neonatal intensive care units (NICU). When catheter-related PCE occurs, timely diagnosis and pericardiocentesis save lives.